Boolean-Based (k, n, m) Multi-Secret Image Sharing - Chien-Chang Chen; Cheng-Shian Lin; Jia-Zhan Chen (Axioms, 2022)
Multi-secret image sharing technology shares multiple secret images among shared images for participants and the recovery requires enough shared images for fulfilling the security property. Simultaneously, the adopted Boolean method preserves high performance. The proposed (k, n, m) multi-secret image sharing scheme shares m secret images among n participants and gathering k participants’ shared images perfectly recovers these m secret images. The proposed scheme exhibits high performance because of the usage of Boolean-based processing. Moreover, the usage of a sharing matrix based strategy acquires perfect reconstruction of the secret images under (k, n) thresholds. Two proposed schemes, the source-random-mixed (SRM) and the source-random-separate (SRS) methods, are presented in this study from different strategies of sharing the random image mixed with the secret images or separated to the secret images, respectively. Moreover, the proposed SRS method exhibits the better sharing capacity. Experimental results show that the proposed schemes perform well on sharing efficiency and security.